The growth plate - Shapiro, Irving M.; Boyan, Barbara; Anderson, H. Clarke (Biomedical and health research, 2002)
Evidence generated by a number of genetic studies indicates that growth is regulated by a number of genes and that interference with their expression can have catastrophic effects on the well being of the whole organism. This work covers skeletal development and growth.